Product Design Training with Solidworks in the Effort of Student Independence at SMK 5 Surakarta - Febrina Agusti; Ringgo Ismoyo Buwono; Adit Tri Wahyono; Defano Putra Ramadana (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
Surakarta 5 Vocational High School was an educational institution committed to improving students' digital skills and adapting to technological developments. In response to the needs and problems faced, this community service activity aims to organize product design training using SolidWorks software for students. This activity was expected to equip students with digital skills that were relevant to the industrial world, while fostering an entrepreneurial spirit. The training method includes delivering material through presentations and direct practice with guidance from lecturers and students. The training lasted for two days in the Mechanical Engineering laboratory of Surakarta 5 Vocational High School. The training was attended by 30 students from the Mechanical Engineering department. The results of this activity include improving students' abilities in using SolidWorks software, mastering digital-based product design techniques, and encouraging entrepreneurial potential through product design services and businesses. Thus, this training provides important provisions for students to be able to face challenges in the world of work or start independent businesses in the field of product design.